Mapping Student Creativity Levels Among Junior High School Students - Andrea, Risa; Hidayati, Novi Wahyu; Hastiani, Hastiani (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2025)
The purpose of this research is to describe the profile of student creativity in P5 (Projek Penguatan Profil Pelajar Pancasila) activities at State Junior High School 1 Sungai Betung and to analyze the creativity program of guidance and counseling teachers in the independent curriculum (Kurikulum Merdeka). In this case, the research informants are three guidance and counseling (BK) teachers in State Junior High School 1 Sungai Betung. Data were collected by conducting observations, interviews, and reviewing programs at State Junior High School 1 Sungai Betung, especially student activities when implementing creativity programs. This method involve documentation related to creativity programs by guidance and counseling teachers, extracurricular activities, P5 activities, guidance and counseling teacher programs such as individual counseling, group counseling and classical guidance, and organized activities related to creativity. The research results show that guidance and counseling teachers play an active role in creativity programs at school. Therefore, guidance and counseling teachers participate in creativity, especially in facilitating extracurricular activities and P5 in the development and growth of students, as well as developing the talents, interests, and potential possessed by students. From the data obtained from interviews, observations, and documentation studies, researchers recommend designing student creativity programs for guidance and counseling teachers so that the existence of this program can develop guidance and counseling teacher programs and students' creativity abilities at school.